Digital participation of left-wing activists in Brazil: cultural events as a cement to mobilization and networked protest - Figeac, Julien; Paton, Nathalie; Peralva, Angelina; Coelho Bezerra, Arthur; Cabanac, Guillaume; Prévost, Héloïse; Ratinaud, Pierre; Salord, Tristan (Brasiliana: Journal for Brazilian Studies, 2021)
This research explores how Brazilian activist groups participate in Facebook to coordinate their social struggles, based on a lexical analysis of publications on 529 pages, published between 2013 and 2017. These groups set up two main repertoires of action by mobilizing Facebook as an arena for challenging political action and a tool for coordinating their mobilizations. This research shows more specifically that artistic expression and the agenda of cultural events are central to these digital action repositories. Publications and conversations related to culture punctuate the ordinary exchange of information between activists, especially during the lulls of social struggles. They structure activist networks on a medium-term basis and contribute to the coordination of social movements by creating the conditions for occasional gatherings, transversal to different types of activism and to various social struggles.